Arterial Pseudoaneurysms Following Hepato-Pancreato-Biliary Surgery: A Single Center Experience - Ielpo, Benedetto; Caruso, Riccardo; Prestera, Antonio; De Luca, Giuseppe Massimiano; Duran, Hipolito; Diaz, Eduardo; Fabra, Isabel; Olivares, Sergio; Quijano, Yolanda; Vicente, Emilio (JOP. Journal of the Pancreas, 2015)
Context Arterial pseudoaneurysm is an uncommon lethal complication following hepato-pancreato-biliary surgery. Objective Aim of this study is to present and discuss the experience of a high volume oncological center. Methods Since 2007 all major surgeries performed at Sanchinarro Oncological Center have been included in a prospective database looking for postoperative arterial pseudonaurysm. Results Until June 2014, among 559 hepato-pancreato-biliary procedures, a total of 14 arterial pseudoaneurysms have been identified (2.5%). Sentinel bleeding was in 57% of cases. Failed arterial embolization occurred in 2 cases. Overall mortality rate was 28.5%. We also identified 3 asymptomatic pseudoaneurysms, one of them managed without embolization, developing a sudden bleeding and died after surgery. Conclusions According to our experience, pseudoaneurysm incidence is higher than reported in current literature and it can be successfully managed through arterial embolization. Furthermore, we found 3 asymptomatic pseudoaneurysms, whose management is still controversial. Image: Bleeding pseudoaneurysm at CT with arterial phase.